Impacts of the entry of the Autonomous Republic of Crimea into the Russian Federation on its tourism industry: An exploratory study. (June 2016) - Ivanov, Stanislav; Idzhylova, Kateryna; Webster, Craig
Abstract: In an unique political scenario, Crimea was integrated into the Russian Federation in 2014, making the legal, political, and economic environment in which the tourism and hospitality industries in Crimea very different from what it had been. In this research, we surveyed the managers of 60 hotels and 31 travel agencies in Crimea to learn about how their businesses were impacted by the Crimea's entry into the Russian Federation and how they have responded to the changes in the macroenvironment. The findings indicate that travel agencies and hoteliers have responded differently to the crisis and have very different concerns regarding the way in which this political event has impacted upon their industries. Highlights: The impacts of Crimea's secession on its tourism industry are investigated. The sample includes 60 hotels and 31 travel agencies. Performance metrics deteriorated in 2014 compared to 2013. Hotels cut prices, travel agencies cut costs.